Afrodiasporic epistemologies and ethnic-racial perspectives: contributions to educational policies in Latin America (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
This article explores Afro-diasporic contributions to the production of knowledge about educational policies with an ethno-racial approach from a Latin American perspective, focusing on Brazil and Colombia. To this end, it analyzes key works from the last 20 years that inform this field, highlighting the main thematic and analytical trends, the actors who have contributed to the development of this field, and the contributions these studies make to the field of educational policies in general. It shows that the study of educational policies with an ethno-racial perspective responds to historical contexts of racial inequality that affect Indigenous and Afro-descendant peoples in the region and has developed in dialogue with the educational practices of the Afro movement, with legislative advances and the creation of specific policies for Afro-descendants in education, as well as with the intervention of agents from international organizations. Keywords: Educational policies. Ethno-racial perspective. Afro-descendants. Afro-diasporic studies. Knowledge production.